Catalog of the subgenus Melanoconion of Culex (Diptera: Culicidae) for South America - Torres-Gutierrez, Carolina; Sallum, Maria Anice Mureb (Zootaxa, 2015)
Species of Culex (Melanoconion) Theobald are recognized as vectors of arboviruses. The species of this subgenus pose a real taxonomic challenge. The current classification of the subgenus recognizes a total of 160 species divided in two major sections, Melanoconion and Spissipes; and several non-formal groupings within each section. We gathered bibliographic records of the subgenus in South America, with particular focus on the period of time after the publication of the Catalog by Pecor et al. (1992) until present time. This compilation included 139 species occurring in South American countries with all the relevant bibliographic sources, including the corresponding information for those medically important species.